Study of performance of aerostat envelope materials on the coast - Lv, Jing; Zhou, Yan; Zhang, Yuanping; Nie, Ying; Wang, Qian (Frontiers in Materials, 2022)
In this article, the performance of several naturally aged envelope materials in Hainan, China, was studied. The results show that the outer layer contributes to the properties of the envelope materials, where PVF and PVDF are better candidates for a weathering layer than TPU and aluminum. Due to the superior water and mildew resistance of PVF and PVDF, the loss of tensile strength for 3216LV and FV1175 was slight, whose value reduced from 101.43 ± 5.45 Kgf/cm and 76.15 ± 3.81 Kgf/cm to 79.73 ± 6.40 Kgf/cm and 70.20 ± 6.57 Kgf/cm, respectively, when aging for 24 months with the helium permeability reduction from 0.8818 L/m2•day•atm and 0.6360 L/m2•day•atm to 0.2047 L/m2•day•atm and 0.2169 L/m2•day•atm aging for 18 months, in the case of FV1175 showed leakage after aging for 24 months due to delamination. However, the tensile strength of HV150 dropped from 82.13 ± 3.61 Kgf/cm to 15.22 ± 2.16 Kgf/cm at 24 months with helium leakage, owing to heavy mildew and degradation. Meanwhile, ETAV150 also exhibited a decreased tensile strength of 57.92 ± 1.32 Kgf/cm after 6 months aging, 32.8% lower than that of the original sample, and showed leakage when aging for 12 months. This research provides a theoretical guidance for the structural design and screen of envelope materials for aerostat used along the coast.